1990
DOI: 10.1139/m90-043
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide induces endotrophic germ tube formation in Candida albicans

Abstract: Candida albicans formed germ tubes when exposed to air containing 5 to 15% carbon dioxide (CO2). The CO2-mediated germ tube formation occurred optimally at 37 degrees C in a pH range of 5.5 to 6.5. No germ tubes were produced at 25 degrees C, even when the optimal concentration of CO2 (10%) was present in the environment. The requirement of CO2 for germ tube formation could be partially substituted by sodium bicarbonate but not by N2. Carbon dioxide was required to be present throughout the entire course of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Australian Dental Journal 1998;43:(1): [45][46][47][48][49][50] C a n d i d a -a s s o c i a ted denture stoma t i t i s . Aetiology and m a n a g e m e n t : A r e v i e w .…”
Section: Introductionmentioning
confidence: 99%
“…Australian Dental Journal 1998;43:(1): [45][46][47][48][49][50] C a n d i d a -a s s o c i a ted denture stoma t i t i s . Aetiology and m a n a g e m e n t : A r e v i e w .…”
Section: Introductionmentioning
confidence: 99%
“…Opportunistic fungal pathogens exposed to ambient air in a natural environmental setting must overcome dramatic changes in CO 2 levels during infection (150-fold change from 0.036 to 5%). In Candida albicans, which causes superficial and systemic candidiasis in immunocompromised patients, high CO 2 levels induce the morphological transition from yeast to hypha that is an important virulence attribute contributing to tissue adhesion and invasion of the pathogen (Sims 1986;Mock et al 1990). Recently it has been reported that CO 2 sensing by C. albicans is mediated by adenylyl cyclase, which produces cAMP, thereby activating protein kinase A (PKA) to trigger filamentous growth (Klengel et al 2005).…”
mentioning
confidence: 99%
“…This effect is due to mechanisms still unknown [21,22]. Mock et al [21] has suggested four possible mechanisms: (1) the variation of endocellular pH, (2) the maintenance of the tricarboxylic acid cycle by anaplerotic reactions, (3) the inhibition or the stimulation of enzymes involved in the morphogenesis, and (4) the regulation of certain genes coding key morphogenic substances. Changes in internal pH, likely related to the activation of proton-pumping by the cytoplasmic membrane ATPases, have been proved to accompany germ-tube emergence in C. albicans [8,9].…”
Section: Discussionmentioning
confidence: 99%